Developing Mental Health Support Chatbots in India: Challenges and Insights - Susmita Halder (Annals of Indian Psychiatry)
Chatbots represent a new perspective in mental health support. The increased use of technology has become a preferred medium for providing mental health services, making it easier to reach a larger population. However, in India, the use of chatbots for mental health support is still in its infancy. There are many reasons behind this. The purpose of this article is to explore and identify the challenges faced by mental health professionals in developing chatbots for mental health support and to examine their future potential.